1998
DOI: 10.1007/s004450050206
|View full text |Cite
|
Sign up to set email alerts
|

Large debris avalanches and associated eruptions in the Holocene eruptive history of Shiveluch Volcano, Kamchatka, Russia

Abstract: Shiveluch Volcano, located in the Central Kamchatka Depression, has experienced multiple flank failures during its lifetime, most recently in 1964. The overlapping deposits of at least 13 large Holocene debris avalanches cover an area of approximately 200 km 2 of the southern sector of the volcano. Deposits of two debris avalanches associated with flank extrusive domes are, in addition, located on its western slope. The maximum travel distance of individual Holocene avalanches exceeds 20 km, and their volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
2
36
1
3
Order By: Relevance
“…4B, C; Table 1; Ponomareva et al, 1998). All Holocene collapses were followed by explosive eruptions, however, the largest plinian eruptions of Shiveluch were not associated with debris avalanches (Ponomareva et al, 1998).…”
Section: Volcanoes Of the Central Kamchatka Depressionmentioning
confidence: 97%
See 4 more Smart Citations
“…4B, C; Table 1; Ponomareva et al, 1998). All Holocene collapses were followed by explosive eruptions, however, the largest plinian eruptions of Shiveluch were not associated with debris avalanches (Ponomareva et al, 1998).…”
Section: Volcanoes Of the Central Kamchatka Depressionmentioning
confidence: 97%
“…Since then, both events have been reinterpreted as sector collapses and the resulting debris avalanche deposits re-examined (Belousov, 1995;Belousov and Belousova, 1998;Melekestsev, 2006). Other work on the CKD volcanoes includes studies of small-volume historical landslides on Kliuchevskoi (Dvigalo and Melekestsev, 2000), pre-historic collapses of Shiveluch (Ponomareva et al, 1998;Belousov et al, 1999) and brief mention of pre-historic collapses on Kamen', Tolbachik (Melekestsev and Braitseva, 1984), Kharchinsky and Zarechny volcanoes (Volynets et al, 1999). In the rest of Kamchatka, only Avachinsky, Bakening and Mutnovsky debris avalanche and landslide deposits have been documented earlier (Melekestsev and Braitseva, 1984;Melekestsev et al, 1992Melekestsev et al, , 1999 although landslide craters have been identified on 22 volcanoes (Leonov, 1995).…”
Section: Geological Background and Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations